Пам'ятки раннього залізного віку в околицях Мотронинського городища - Ляшко, Ю.Ю. (Археологія і давня історія України, 2018)
Статтю присвячено пам'яткам раннього залізного віку, які були виявлені в околицях Мотронинського городища. Motroninsky ancient settlement belongs to the
most famous monuments of the Scythian epoch of
the Dnieper Forest-Steppe Right Bank. Since the late
1980s and until today, work is underway to study the
monuments of this time in the vicinity of the site of
the ancient settlement. This work is based on materials
that identify the chronological and periodic frames
of the surveyed monuments. In total 21 settlements of Scythian time of VII—III centuries BC were surveyed
and opened. The results of this work confirm the version of the researchers of the site of ancient settlement
that its main population lived outside the fortification in a radius of several kilometers.